STRATEGI GURU DALAM MENINGKATKAN MUTU PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI MTs NEGERI BATU PADA ERA MILENIAL - Nadila Farkhatun Amalda; Moh Muslim; Atika Zuhrotus Sufiyana (VICRATINA, 2022)
This study uses a descriptive qualitative research approach. The purpose of this study was to describe the planning, implementation, and evaluation of the application of students' spiritual attitudes at MTs Negeri Batu. In this study, the researcher acted as an instrument as well as data collection. The results of the research that has been carried out are 1) Planning for the application of spiritual attitudes carried out by Islamic Religious Education teachers at MTs Negeri Batu by designing a learning implementation plan (RPP), determining KI-1 attitude indicators, and planning habituation; 2) Implementation of the application of spiritual attitudes carried out by the teacher carrying out habits such as: prayer at the beginning and after the learning process, reading tahlil, reading the Qur'an, praying dhuha, praying duhur, applying 5s (smile, greeting, greeting, polite , polite), implementing the 5m Health protocol